THE DIFFERENCES OF LEARNING STRATEGIES AND ACHIEVEMENTS BETWEEN STUDENTS WHO TAKE ENGLISH COURSES AND WHO DO NOT TAKE ENGLISH COURSES IN LEARNING VOCABULARY - Dewa, Muh. Tegar Indar; Farahdiba, Syarifah; Ariyani, Amra (Universitas Negeri Makassar, 2023)
The purpose of this study is to discover the differences of learning strategies and learning achievements between students who take English courses and who do not take English courses in learning vocabulary. The researcher applied quantitative research causal-comparative type. There were 20 students from grade VIII SMPN 2 Sungguminasa academic year 2023/2024 chosen by purposive sampling. The data were obtained by giving questionnaire and vocabulary test. Then the data was analyzed by using descriptive statistics and t-test. The results show the learning strategies has the probability value = 0.037 that was lower than the level of significance value = 0.05. It was proved by the average score of students who take English courses (102.90) that is bigger than students who do not take English courses (83.00). The learning achievements also has the probability value = 0.005 that was lower than the level of significance value = 0.05. It was also proved by mean score of students who take English courses (89.10) that is bigger than students who do not take English courses (58.60). In conclusion, there are differences of learning strategies and learning achievements between students who take English courses and those who do not take English courses in learning vocabulary.